L-carnitine supplementation attenuates NAFLD progression and cardiac dysfunction in a mouse model fed with methionine and choline-deficient diet. Issue 3 (March 2020) - Mollica, Giulia; Senesi, Pamela; Codella, Roberto; Vacante, Fernanda; Montesano, Anna; Luzi, Livio; Terruzzi, Ileana
Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disorder. NAFLD, associated lipotoxicity, fibrosis, oxidative stress, and altered mitochondrial metabolism, is responsible for systemic inflammation, which contributes to organ dysfunction in extrahepatic tissues, including the heart. We investigated the ability of L-carnitine (LC) to oppose the pathogenic mechanisms underlying NAFLD progression and associated heart dysfunction, in a mouse model of methionine-choline-deficient diet (MCDD). Mice were divided into three groups: namely, the control group (CONTR) fed with a regular diet and two groups fed with MCDD for 6 weeks. In the last 3 weeks, one of the MCDD groups received LC (200 mg/kg each day) through drinking water (MCDD + LC). The hepatic lipid accumulation and oxidative stress decreased after LC supplementation, which also reduced hepatic fibrosis via modulation of α-smooth muscle actin (αSMA), peroxisome-activated receptor gamma (PPARγ), and nuclear factor kappa B (NfƙB) expression. LC ameliorated systemic inflammation, mitigated cardiac reactive oxygen species (ROS) production, and prevented fibrosis progression by acting on signal transducer and activator of transcription 3 (STAT3), extracellular signal-regulated kinase 1-2 (ERK1-2), and αSMA. This study confirms the existence of a relationship between fatty liver disease and cardiac abnormalities and highlights the role of LC in controlling liver oxidative stress, steatosis, fibrosis, and NAFLD-associated cardiac dysfunction.